Development and validation of an HPLC–MS/MS method to simultaneously quantify alectinib, crizotinib, erlotinib, gefitinib and osimertinib in human plasma samples, using one assay run. (31st August 2021) - van Veelen, Ard; van Geel, Robin; Schoufs, Roy; de Beer, Yvo; Stolk, Leo M.; Hendriks, Lizza E. L.; Croes, Sander
Abstract: A liquid chromatography–tandem mass spectrometry method was developed and validated to quantify alectinib, crizotinib, erlotinib and gefitinib. This assay can be combined with our method for osimertinib, allowing quantification of the most used ALK ‐ and EGFR ‐tyrosine kinase inhibitors (TKIs) in non‐small cell lung cancer with a single‐assay setup. Chromatographic separation was performed on a HyPurity® C18 analytical column using an elution gradient of ammonium acetate in water and in methanol, both acidified with formic acid 0.1%. Detection and quantification were performed using a triple quad mass spectrometer with an electrospray ionization interface. This method led to robust results, as the selectivity, carryover, precision and accuracy met all pre‐specified requirements. The assay was validated over a linear range of 100–2, 000 ng/ml for alectinib and erlotinib and 50–1, 000 ng/ml for crizotinib and gefitinib. Alectinib, crizotinib, erlotinib and gefitinib were all stable for at least 4 h in whole blood (at room temperature and at 4°C) and for at least 1 month in EDTA plasma when stored at −80°C, while osimertinib proved to be unstable at room temperature. Although high‐performance liquid chromatography was used, the run time was short and comparable with other methods using ultra‐high performance liquid chromatography.